2022
DOI: 10.1155/2022/1546734
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Ginger (Zingiber officinale) Extract Ameliorates the Harmful Effects of High-Dose Lornoxicam in Albino Male Rats

Abstract: Lornoxicam is a potent oxicam-class nonsteroidal anti-inflammatory drug (NSAID) with analgesic, anti-inflammatory, and antipyretic effects. Its impacts on many biological functions are not fully understood. We measured various biomarkers in male albino rats provided an oral aqueous ginger extract before IM administration of therapeutic and 2× the therapeutic doses of lornoxicam. The aqueous ginger plant extract was characterized by mass spectroscopy, and its effects were determined by examining free radical sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…This study revealed that ginger significantly ameliorated the histological and ultrastructural effects induced by labetalol in fetal renal tissue. Many recent studies confirmed the therapeutic effect of ginger against nephrotoxicity (Dawood et al, 2022;El-Bahr et al, 2022). Ali et al (2020) reported that the ethanolic extract of Z. officinale (200 mg orally for 8 weeks) had a protective effect on the renal damage induced by mercuric chloride in rats.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This study revealed that ginger significantly ameliorated the histological and ultrastructural effects induced by labetalol in fetal renal tissue. Many recent studies confirmed the therapeutic effect of ginger against nephrotoxicity (Dawood et al, 2022;El-Bahr et al, 2022). Ali et al (2020) reported that the ethanolic extract of Z. officinale (200 mg orally for 8 weeks) had a protective effect on the renal damage induced by mercuric chloride in rats.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, ginger treatment during pregnancy does not increase the risk of congenital malformations, stillbirth, perinatal death, preterm birth, or low birth weight (Weidner and Sigwart, 2000;Heitmann et al, 2013). Furthermore, the therapeutic role of ginger against renal damage has been demonstrated (Tzeng et al, 2013;Gholampour et al, 2017;Pratap et al, 2017;El-Bahr et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The ginger and propolis extracts were gathered from the local market at Alexandria, identified by botanists at the faculty of Agriculture Alexandria University, then air-dried and ground into fine powder. At room temperature, 150 g of ginger powder was macerated in 200 mL of distilled water for 24 h, then filtered and concentrated in a rotary evaporator to obtain the final ginger aqueous extract ( El-Bahr et al, 2022 ). About 200 g of propolis powder was soaked in 500 mL distilled water for 2 h at 70°C under the filtered and concentrated stirring to obtain the final propolis aqueous extract ( de Moura et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%